The Society’s Perception of Maddoa’ Ceremony in Enrekang South Sulawesi - M. Musyarif; Muh. Shaleh; A. Ahdar; N. Nirwana (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
Maddoa’ is a traditional ceremony for society after conducting harvest rice in Enrekang South Sulawesi. It is an expression of joy and gratitude towards God Almighty for the success of farming. It has many values in social, cultural and religious lives and provides benefits for people’s life.  This research discusses the process of carrying the traditional ceremony and the perception of society toward Maddoa’ in Kaju Bulo Village, Enrekang Regency, South Sulawesi. This research employs qualitative method with anthropology, sociology, and the phenomenology of religious approach. Thus, the data collected through observation, interview, and documentation. The result showed that Maddoa’ is held in the month of Muharram every Friday. It is held with other ceremonies of Mappadendang, Mappasosso, and eating together on the last day. The Maddoa’ gives various perception from society in Kaju Bulo village, Enrekang Regency, South Sulawesi. The Maddoa’ contained many values that must be preserved by the next generation. The values were friendship, unity, cooperation, and solidarity.